1998
DOI: 10.1162/002081898550770
|View full text |Cite
|
Sign up to set email alerts
|

What Makes the World Hang Together? Neo-utilitarianism and the Social Constructivist Challenge

Abstract: Social constructivism in international relations has come into its own during the past decade, not only as a metatheoretical critique of currently dominant neo-utilitarian approaches (neo-realism and neoliberal institutionalism) but increasingly in the form of detailed empirical findings and theoretical insights. Constructivism addresses many of the same issues addressed by neo-utilitarianism, though from a different vantage and, therefore, with different effect. It also concerns itself with issues that neo-ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
241
0
29

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 835 publications
(284 citation statements)
references
References 471 publications
1
241
0
29
Order By: Relevance
“…may become advocates for a given policy, providing seemingly disinterested and objective analysis of its benefits+ Students of epistemic communities postulate that policy professionals, academics, international nongovernmental organizations INGOs!, and NGOs can influence governments to adopt new policies simply by making arguments for them+ 85 Epistemic communities not only help to define new solutions to existing problems~for example, central bank independence as a solution to inflation! but also identify new problems and propose solutions to them~for example, global warming and the Kyoto protocols!+ The epistemic community of American economists is often seen to have played a critical role in economic liberalization in Latin America and beyond+ 86 It may be that Latin American countries sent economics students to the University of Chicago because they wanted, ex ante, to join the liberal bandwagon driven by Friedman and colleagues+ This would suggest that North American economists had an effect on Latin American economic policies, but that their influence operated through the preferences of national leaders who sent deputy finance ministers to train in the United States, rather than through the preferences of newly minted Chicago School graduates themselves+ Either way, the community of economists has arguably shaped new policy norms+ Whereas conventional logic-of-development arguments suggest that countries will adopt certain programs when they are developmentally ready for them, world polity theorists have found that countries embrace new norms for symbolic reasons, even when they cannot begin to put them into practice+ This is particularly true of social welfare policies and human rights+ Strang and Chang, for example, find that large numbers of countries ratified International Labor Organization treaties guaranteeing welfare rights, but that only in developed countries did ratification lead to increased welfare expenditures+ Developing countries signed the treaty even though they lacked the resources to carry through+ This may not represent bad faith so much as the power of new international norms even in countries that are not developmentally capable of implementing them+ 87 Even in the realm of 83+ See Finnemore and Sikkink 2001;Ruggie 1998;and Wendt 1999+ 84+ Haveman 1993+ 85+ See Haas 1959Mintrom 1997;and Mintrom and Vergari 1998+ 86+ Numerous studies have purported to show, for example, the influence of "Chicago boys" in economic policy change in Latin America, either directly or indirectly+ See Drake 1994;Harberger 1997;Montecinos 1997;andMurillo 2002+ 87+ Strang andChang 1993+ economic policy, countries may adopt new global norms before they are really ready+ The other principal emulation approach draws on reference group theory in social psychology+ From this perspective, individuals emulate the behavior of their selfidentified peers, even when they cannot ascertain that doing so will in fact be in their best interests+ At the international level, sociocultural linkages~common language, history, religion, and so on! may contribute to "psychological proximity" among nations+ 88 Indeed, many cross-national analy...…”
Section: Emulationmentioning
confidence: 99%
“…may become advocates for a given policy, providing seemingly disinterested and objective analysis of its benefits+ Students of epistemic communities postulate that policy professionals, academics, international nongovernmental organizations INGOs!, and NGOs can influence governments to adopt new policies simply by making arguments for them+ 85 Epistemic communities not only help to define new solutions to existing problems~for example, central bank independence as a solution to inflation! but also identify new problems and propose solutions to them~for example, global warming and the Kyoto protocols!+ The epistemic community of American economists is often seen to have played a critical role in economic liberalization in Latin America and beyond+ 86 It may be that Latin American countries sent economics students to the University of Chicago because they wanted, ex ante, to join the liberal bandwagon driven by Friedman and colleagues+ This would suggest that North American economists had an effect on Latin American economic policies, but that their influence operated through the preferences of national leaders who sent deputy finance ministers to train in the United States, rather than through the preferences of newly minted Chicago School graduates themselves+ Either way, the community of economists has arguably shaped new policy norms+ Whereas conventional logic-of-development arguments suggest that countries will adopt certain programs when they are developmentally ready for them, world polity theorists have found that countries embrace new norms for symbolic reasons, even when they cannot begin to put them into practice+ This is particularly true of social welfare policies and human rights+ Strang and Chang, for example, find that large numbers of countries ratified International Labor Organization treaties guaranteeing welfare rights, but that only in developed countries did ratification lead to increased welfare expenditures+ Developing countries signed the treaty even though they lacked the resources to carry through+ This may not represent bad faith so much as the power of new international norms even in countries that are not developmentally capable of implementing them+ 87 Even in the realm of 83+ See Finnemore and Sikkink 2001;Ruggie 1998;and Wendt 1999+ 84+ Haveman 1993+ 85+ See Haas 1959Mintrom 1997;and Mintrom and Vergari 1998+ 86+ Numerous studies have purported to show, for example, the influence of "Chicago boys" in economic policy change in Latin America, either directly or indirectly+ See Drake 1994;Harberger 1997;Montecinos 1997;andMurillo 2002+ 87+ Strang andChang 1993+ economic policy, countries may adopt new global norms before they are really ready+ The other principal emulation approach draws on reference group theory in social psychology+ From this perspective, individuals emulate the behavior of their selfidentified peers, even when they cannot ascertain that doing so will in fact be in their best interests+ At the international level, sociocultural linkages~common language, history, religion, and so on! may contribute to "psychological proximity" among nations+ 88 Indeed, many cross-national analy...…”
Section: Emulationmentioning
confidence: 99%
“…Ultimately though, as global governance became both the question and the answer to "what makes the world hang together" (Ruggie, 1998), for many it never fully realized its value as an analytical tool precisely because it failed to develop a theory of global order and transformation. While "[t]he strand of thinking about world politics as global governance that comes closest to a theory is essentially linked to the work of Rosenau" (Dingwerth and Pattberg, 2006: 189), most agree with Smouts (1998: 81) who argues that global governance remains for the most part a descriptive account which in the end "betokens no major epistemological breakthrough".…”
Section: Current Understandings In and Of Global Governancementioning
confidence: 99%
“…This emphasis on civil society (power to citizens) enabled by networks, democratization and globalization parallels that of PVM/Governance/NPS in PAM and can be argued as an outcome of the intellectual influence of Jurgen Habermas"s Frankfurt School of Critical Theory (Cox, 1983) from Sociology (Gottlieb, 1981). Second, Social Constructivists (Wendt, 1992;Wendt, 1999;Adler, 1997;Ruggie, 1998) argued that "anarchy is what states made of it" and that international politics is socially 5 Syracuse University Minnowbrook Conference since late 1960s have actively challenged the orthodoxy with its core ideas in postmodern public administration such as public administration cannot be neutral; technology is dehumanizing; public administration must be built on post-behaviorial and post-positivist logic of more democratic, more adaptable, more responsible to changing social, economic and political circumstances (Frederickson & Smith, 2003, p. 128;Anonymous, 2011). constructed by ideas (Goldstein & Keohane, 1993), interests (Finnemore, 1996), culture (Katzenstein, 1996) and norms (Barkin & Cronin, 1994), rather than "out there to be discovered" in the (positivist) natural sciences. Social Constructivism can be seen as a response to agency-structure debate; instead of arguing primacy of either agency or structure, social constructivism focuses on interactions (Giddens, 1984;Bathlet & Gluckler, 2011, pp.…”
Section: Globalization: Post-positivismmentioning
confidence: 99%